Patient-reported impact of symptoms in schizophrenia scale (PRISS): Development and validation - Moreno-Kustner, Berta; Fábrega-Ruz, Julia; Gonzalez-Caballero; Reyes-Martin, Sara; Ochoa, Susana; Romero-Lopez-Alberca, Cristina; Cid, Jordi; Vila-Badia, Regina; Frigola-Capell, Eva; Salvador-Carulla, Luis (Wiley, 2022)
Background We report the psychometric properties of the Patient-Reported Impact of Symptoms in Schizophrenia Scale (PRISS), which assesses the impact of subjective experiences or qualia in outpatients with this condition. Methods A cross-sectional study was carried out in 162 patients diagnosed with schizophrenia in Spain. The PRISS measures the presence, frequency, concern and interference with daily life of self-reported experiences related to the main symptoms observed in these patients. The psychometric analysis included test-retest reliability, internal consistency and structural and convergent validity. Results The 28-item PRISS showed good test-retest reliability as 64.3% of the intraclass correlation coefficient values were between 0.40 and 0.79, which were statistically significant (p < 0.01). Analysis of the structural validity revealed a three-factor structure, (1) productive subjective experiences, (2) affective-negative subjective experiences and (3) excitation, which accounted for 56.11% of the variance. Of the Pearson's correlation coefficients analysed between the PRISS and the Positive and Negative Syndrome Scale (PANSS), Scale for Assessment of Negative Symptoms (SANS) and World Health Organization Disability Assessment Schedule (WHO-DAS), 72.2% were statistically significant (p < 0.05) and ranged from 0.38–0.42, 0.32–0.42 and 0.40–0.42, respectively. Conclusion Our results indicate that the PRISS appears to be a brief, reliable and valid scale to measure subjective experiences in schizophrenia and provides valuable information complementary to clinical evaluation.
Keywords: Esquizofrenia; Patient- reported outcome; Patient- reported outcome measure; Schizophrenia; Subjective experiences